Study on the viability of unprotected bacterial spores directly embedded in a reactive magnesia cement matrix for potential crack healing - Xiao, Xi (2022)
Due to the harsh environment of Portland cement (PC), bacteria spores are often protected by porous carriers or encapsulated with soft materials before incorporated in PC concrete for self-healing. However, this often leads to strength reduction of concrete and higher cost. This paper investigated the feasibility of direct addition of unprotected bacteria spores into reactive magnesia cement (RMC) for potential crack healing via microbial-induced carbonate precipitation (MICP) of Bacillus cohnii with magnesium lactate. To examine the bacteria survival and precipitation capability in the matrix, spores were incorporated directly into RMC pastes. Strong MICP evidenced by the massive formation of nesquehonite to fully close the crack was observed in the hardened RMC paste with unprotected bacteria spores addition, which was associated with the high viability of bacteria in dry and low alkaline RMC environment. This study presented a novel finding for the feasibility of the direct incorporation of unprotected bacteria spores for potential crack healing.